The Mediating Role of Management Accounting Information Systems : Innovation Capability and Firm Performance - Carolina, Yenni; Joni, J; Jerry, J (Universitas Pendidikan Indonesia, 2024)
Main Purpose: This study aims to analysed the impact of innovation capability on financial firm performance, with management accounting information systems (MAIS) as a mediating variable.Method: The research employs a causal-explanatory approach with a quantitative method. Data was collected using surveys distributed via Google Forms and physical questionnaires, and analysed using Structural Equation Modelling (SEM): SMARTPLS.Main Finding: The study finds that innovation capability positively influences firm performance, both directly and indirectly, through MAIS. MAIS also has a significant positive effect on firm performance. Additionally, MAIS mediates the relationship between innovation capability and firm performance, reinforcing the role of accounting information systems in enhancing financial outcomes.Theory and Practical Implications: The findings contribute to the theoretical understanding of the role of MAIS as a mediator in the relationship between innovation and firm performance. Practically, it provides insights for startup companies to leverage innovation capabilities while integrating robust MAIS to improve financial performance.Novelty: This research fills a gap by examining the mediating role of MAIS in the relationship between innovation capability and firm performance in startup companies, an area that has been largely unexplored.